Adaptasi Sumber Daya Manusia Melalui Transformasi Digitalisasi Berbasis Artificial Intelligence (AI) Pelaku UMKM Kabupaten Gowa - Rahim, Abd; Jam’an, Andi; Muchran, Muchriady (Universitas Batanghari Jambi, 2025)
This study aims to analyze the adoption level, implementation, and the challenges and barriers to human resource (HR) adaptation in applying AI-based digital transformation among MSMEs in Gowa Regency. A qualitative descriptive method was employed, with data collected through in-depth interviews and participatory observation. The findings reveal varying levels of AI adoption among MSMEs. MSMEs engaged in screen printing and digital printing have started leveraging technologies such as Bing Image Creator to streamline graphic design processes, while the majority still face technological literacy barriers. Major challenges include limited knowledge, a digital divide between urban and rural areas, and a lack of technological skills. The study emphasizes the critical role of HR development through digital literacy training and technological infrastructure support. Therefore, an integrated strategy involving the government, educational institutions, and MSMEs is essential to fully capitalize on AI-based digital transformation benefits.